Seroprevalence of Toxoplasma, Rubella, CMV and HSV infection at a teaching hospital: A 7 year study from North India - Dinkar, Anju (J Family Med Prim Care, 2020)
OBJECTIVES: The present study was aimed to find seroprevalence in different age group population to explore the burden of TORCH (toxoplasma, rubella virus, cytomegalovirus [(CMV] and herpes simplex virus [HSV]) infection in the North Indian Population. MATERIALS AND METHODS: It is a retrospective study carried out in the Microbiology Department, Institute of Medical Science, Banaras Hindu University (IMS, BHU), a tertiary care centre of North India. The blood samples of the suspected population of either sex or age group from different departments were analysed over a period of 7 years. The samples were tested for TORCH infections by the IgM ELISA kit following the manufactures instruction. RESULTS: Out of total 4044 samples, 1353 (33.46%) cases were seropositive with maximum cases from the obstetrics and gynaecology department 39.46%. The highest seropositivity of TORCH (43.15%) was in the age group 15–25 years followed by 36.33% in the age group 25–35 years. This study revealed an overall male and female ratio of the total positive cases as 0.12 while it was 2.2 for pediatric cases (0–15 years). The overall seroprevalence was contributed as toxoplasma 1.38%, rubella 1.14%, CMV 13.63% and herpes 17.43%. The overall seropositivity (IgM) contributed as toxoplasma gondii with 4%, rubella with 3%, cytomegalovirus with 41% and herpes simplex virus with 52%. The coinfection of HSV with CMV was most abundant with 246 cases. CONCLUSIONS: The seropositivity of toxoplasma and rubella were comparatively more in infants while CMV and herpes were more prevalent in adults. Though, the incidence of TORCH has reduced over the past few years. Furthermore, knowing the epidemiology is an important aspect to develop strategies and appropriate implementation for the prevention of infection.